Fenomena Menghafal Al-Qur’an di Pondok Pesantren: Studi Kasus Ma’had Mambaul Qur’an Wonosobo Jawa Tengah - Arba'atul Husna; Mukromin; Ashief El Qorny (Bulletin of Indonesian Islamic Studies, 2022)
This article aims to investigate the process of memorizing the Qur'an for students at Ma'had Mambaul Qur'an Munggang Bawah Wonosobo. In addition, this article aims to investigate students' problems in memorizing the Qur'an and their solutions. This article uses a qualitative field research type with documentation, interviews, and observation data collection methods. Then, the source of the data was obtained through information from the Board of Directors of the Islamic Boarding School and the tahfiz students. The results showed that the tahfiz program at Ma'had Mambaul Qur'an was good with the mainstay program of muraja’ah and semesterly tasmi'. The problems experienced by students in memorizing the Qur'an are laziness, the influence of technology especially handphones, and inconsistent management programs. The solution for students to face these problems is to motivate themselves to be more active in memorizing and to arrange a conducive time for memorizing.